A Dramaturgy of Death: Performing (And Spectating) Filial Piety in Early China. Issue 2 (July 2022) - Radice, Thomas
Abstract: This essay analyzes the early Chinese elite discourse on filial death rituals, arguing that early Chinese texts depict these rituals as performance events. Building on spectacle of xiao sacrifices in the Western Zhou Dynasty, Eastern Zhou authors conceived of filial death rituals as dramaturgical phenomena that underscored not only what needed to be performed, but also how it should be performed, and led to an important distinction between personal dispositions and inherited ritual protocol. This distinction, then, led to concerns about artifice in human behavior, both inside and outside the Ruist (Confucian) tradition. By end of the Warring States Period and in the early Western Han Dynasty, with the embracement of artifice in self-cultivation, the dramatic role of the filial son in death rituals became even more developed and complex, requiring the role of cultivated spectators to be engaged critics who recognized the nuances of cultivated performances.